The role of tumor-associated macrophages in the progression, prognosis and treatment of endometrial cancer - Sun, Yihan; Jiang, Genyi; Wu, Qianhua; Ye, Lei; Li, Bilan (Frontiers in Oncology, 2023)
Tumor-associated macrophages (TAMs) are the main immune cells in the tumor microenvironment (TME) of endometrial cancer (EC). TAMs recruitment and polarization in EC is regulated by the TME of EC, culminating in a predominantly M2-like macrophage infiltration. TAMs promote lymphatic angiogenesis through cytokine secretion, aid immune escape of EC cells by synergizing with other immune cells, and contribute to the development of EC through secretion of exosomes so as to promoting EC development. EC is a hormone-and metabolism-dependent cancer, and TAMs promote EC through interactions on estrogen receptor (ER) and metabolic factors such as the metabolism of glucose, lipids, and amino acids. In addition, we have explored the predictive significance of some TAM-related indicators for EC prognosis, and TAMs show remarkable promise as a target for EC immunotherapy.